Normal brain imaging accompanies neuroimmunologically justified, autoimmune encephalomyelitis. Issue 3 (May 2018) - Takewaki, Daiki; Lin, Youwei; Sato, Wakiro; Ono, Hirohiko; Nakamura, Masakazu; Araki, Manabu; Okamoto, Tomoko; Takahashi, Yuji; Kimura, Yukio; Ota, Miho; Sato, Noriko; Yamamura, Takashi
Abstract : Objective: To examine cases with a clinical course, signs, and symptoms mimicking MS, but without abnormalities on conventional MRI. Methods: Among 550 people with a tentative diagnosis of MS or neuromyelitis optica spectrum disorder (NMOSD), we selected patients, who met the 2010 McDonald diagnosis criteria for MS, but did not show abnormal findings on conventional brain and spinal cord MRI. After evaluating their clinical data, we analyzed fractional anisotropy (FA) values in the brain white matter on diffusion tensor MRIs and the frequencies of B-cell subsets in the peripheral blood in the corresponding cases as compared to healthy controls. Results: Eleven patients (age: 41.1 ± 8.0 years, 9 women and 2 men) met the selection criteria. They were functionally disabled, with a median expanded disability status scale score of 6.0 (2.0–8.0). CSF oligoclonal bands were negative in all cases. IV methylprednisolone and plasmapheresis (PP) were found to be efficacious. Diffusion tensor MRI analysis revealed extensive white matter abnormalities characterized by significantly decreased FA values. The frequency of plasmablasts in the peripheral blood was significantly increased in these patients similar to NMOSD. Conclusions: The neurologic disabilities in these patients could be ascribed to brain white matter damage, as revealed by MRI analysis, whereas the efficacy of PP and B-cell abnormalities in the patients suggested an autoimmune-mediated pathogenesis. In the differential diagnosis of MS, we propose that this condition be referred to as, "Normal-appearing Imaging-associated, Neuroimmunologically Justified, Autoimmune encephalomyelitis."